How to improve public health centers' service capacity and their accessibility for people living in remote border regions: The case study of Sambas District of West Kalimantan - Ika Ardina (BKM Public Health and Community Medicine, 2021)
Purpose: To examine service capacity, availability, accessibility, and utilization of public health centers, and explore their improvement options for public health centers in the remote border district of Sambas. Method: This qualitative study used in-depth interviews of local stakeholders, field observation, and documentary reviews. Results: People living in remote border areas have difficulties accessing quality primary health services. It was because of the geographical condition, topography, transportation, communication access, the high level of poverty of the population, knowledge, and various social issues that they were facing. Meanwhile, the availability of human health resources at the public health center was not adequate, and the standard of the minimum staff types was still not fulfilled yet. The limited availability of human health resources is because of the moratorium on health workers. Likewise, the availability of supporting facilities and infrastructure still varies between health facilities. Meanwhile, medical equipment is still not fully fulfilled in primary health facilities. These things affected the quality and level of service. As an effort to overcome development inequality, Indonesia speeds up development in Remote Area Borders and Islands. Specific interventions have been carried out through various programs such as Nusantara Sehat to fill the lack of human health resources. In Sambas District, fulfillment of health services to obtain strategies and policy options related to health services at the remote border regions' health centers was still not optimal. Local governments have not properly fulfilled the availability of facilities and infrastructure for health services at the public health center and its network. The availability of public health center officers at the Remote Area Borders who are not under the duties and needs of fulfilling Health Human Resources in a primary health service. Conclusion: Health services at the remote border regions' health centers were strongly influenced by various factors, especially access and service capacity, which became obstacles to the health service process, more facilities are needed, and the attention of the central and local governments in policy options related to the remote border area health centers.